The Effect of Labor Market Conditions at Entry on Workers' Long-Term Skills - Jaime Arellano-Bover (Institute of Labor Economics (IZA), 2020)
This paper studies the impact of labor market conditions during the education-to-work transition on workers' long-term skill development. Using representative survey data on measures of work-relevant cognitive skills for adults from 19 countries, I document four main findings: i) cohorts of workers who faced higher unemployment rates at ages 18–25 have lower skills at ages 36–59; ii) unemployment rates faced at later ages (26–35) do not have such an effect; iii) the former findings hold even though, on average, people get more formal education as a response to higher unemployment in their late teens and early twenties; iv) skill inequality is affected: workers whose parents were less educated bear most of the negative effects. These findings can be rationalized by on-the-job learning during the early twenties being an important factor of skill-development, and such learning being negatively impacted by bad macroeconomic conditions. Using German panel data on skills, I show that young workers at large firms experience higher skill growth than those at small firms. This finding suggests firm heterogeneity in human capital provision to young workers as a potential mechanism since, in bad economic times, young workers disproportionately match with small firms.
Keywords: J24; J23; E24; 330; labor market entry; macroeconomic conditions; measures of skills; cognitive skills; on-the-job learning; firms